Dreaming of God and the role of faith in everyday life: an empirical study - Schredl, Michael; Mönch, Jan-Hendrik (Pastoral psychology, 2023)
In Christian faith, dreams - at least some - have been seen as messages from God; very powerful examples can be found in the Bible. However, empirical research regarding dreams of God is relatively scarce. Four hundred and fifty-two persons participated in the present survey, including a group from theology-related professions (theology students, priests, etc.). The findings indicate that the belief that dreams can be messages from God is related to the importance of faith in the everyday life of the dreamer and a positive attitude towards dreams. About 20% of the participants reported having dreams about encountering God, which was related to their waking life religiosity. On the one hand, the findings support the continuity hypothesis of dreaming, that is, that dreaming reflects waking life, while, on the other hand, these special dreams might help the dreamer to deepen their faith. Longitudinal studies are necessary to study this bidirectional relationship between waking life faith and religious dreams.